OPTIMALISASI ZAKAT MELALUI STRATEGI DISTRIBUSI DALAM MEWUJUDKAN KESEJAHTERAAN MASYARAKAT YANG TEPAT SASARAN - Hasan; Mugiyati (Qolamuna : Jurnal Studi Islam, 2026)
Zakat is a key pillar in Islam with a strategic function as an instrument of wealth redistribution to reduce poverty and improve community welfare. Although the potential of zakat in Indonesia is estimated to reach hundreds of trillions of rupiah, the realization of community welfare through consumptive and productive approaches. The research method used is literature review, year, the realization of its management is still not optimal. This study aims to analyze effective zakat distribution strategies in the media by collecting data from reliable literature, including journals, books, and official reports. The result of the study shows that productive-based zakat distribution has more sustainable impact in empowering mustahik and alleviating poverty. In addition, collaboration between zakat institutions, government, private sector, and society plays an important role in optimizing zakat management. With the right approach, zakat can be a real solution in creating social justice and equitable welfare. Keywords : Zakat, Distribution, Welfare, Empowerment